Effect of bullfrog (Rana catesbeiana) oil administered by gavage on the fatty acid composition and oxidative stress of mouse liver - Silva, L.P. (2004)
The aim of the present study was to investigate the effects of daily intragastric administration of bullfrog oil (oleic, linoleic and palmitoleic acid-rich oil), corresponding to 0.4% of body weight for four weeks, on fatty acid composition and oxidative stress (lipid peroxidation and catalase activity) in mouse liver. The activities of aspartate aminotransferase (AST), alkaline phosphatase (ALP), alanine aminotransferase (ALT), and gamma-glutamyltransferase (GGT), biomarkers of tissue injury, were determined in liver homogenates and serum. The proportions of 18:2n-6, 20:4n-6, 20:5n-3, and 22:6n-3 (polyunsaturated fatty acids, from 37 to 60%) in the total fatty acid content were increased in the liver of the bullfrog oil-treated group (P < 0.05) compared to control. At the same time, a significant decrease in the relative abundance of 14:0, 16:0, and 18:0 (saturated fatty acids, from 49 to 25%) was observed. The hepatic content of thiobarbituric acid reactive substances (TBARS) was increased from 2.3 ± 0.2 to 12.3 ± 0.3 nmol TBA-MDA/mg protein and catalase activity was increased from 840 ± 32 to 1110 ± 45 µmol reduced H2O2 min-1 mg protein-1 in the treated group. Bullfrog oil administration increased AST and ALP activities in the liver (from 234.10 ± 0.12 to 342.84 ± 0.13 and 9.38 ± 0.60 to 20.06 ± 0.27 U/g, respectively) and in serum (from 95.41 ± 6.13 to 120.32 ± 3.15 and 234.75 ± 11.5 to 254.41 ± 2.73 U/l, respectively), suggesting that this treatment induced tissue damage. ALT activity was increased from 287.28 ± 0.29 to 315.98 ± 0.34 U/g in the liver but remained unchanged in serum, whereas the GGT activity was not affected by bullfrog oil treatment. Therefore, despite the interesting modulation of fatty acids by bullfrog oil, a possible therapeutic use requires care since some adverse effects were observed in liver.